PENGGUNAANJSP(JAVASERVER PAGES) SEBAGAIAPLIKASIPEMASARANBERBASIS WEB (Information Technology and Telematics, 2016)
Competition between companies increasing lystringent After passing through the era of the global marketing 2013. In marketing its products, a company must be able to make the right  target.  The  growth  of  information  technology is currently widely hange the marketing system as well as the sale of a product.  By sitting in front of a computer, a person can obtain marketing information products.  This is a benefit of adannya website as ameans of promotion.  Marketing system which runs today by working with government and private agencies toprint blank certificate. Because the price in this printing is cheaper compared to other printing, so many companies are throwing colleagues workto hare thework.  The existing system is less optimal, because the existing customers only among peer printing only. This study aims to create a Web-Based Marketing Applications with  programming JSP (Java  Server Pages). With this website is expected to help the company in introducing his own efforts so that customers can directly orderto CV Action circum ference. Keywords:Aplikasipemasaran, CV.LingkarAksiUngaran, JSP(Java Server Pages).